ANALYZING UTILITARIAN AND HEDONIC VALUE BETWEEN MALE AND FEMALE CUSTOMERS OF EXCELSO MANADO TOWN SQUARE - Palilingan, Vanessa Natalisa; Tumbuan, W.J.F Alfa; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2017)
Abstract: Study found Coffee has now become part of the lifestyle. People come to the Excelso not simply want to drink coffee, but because there is a touch of emotion, whether it’s a feeling of pride, prestige, or the warmth of one of the strategic steps performed by the provider of the Excelso Coffee shop. By knowing the values, excelso can increase customer to keep win the market share and be better than competitors. This research focuses on customers of Excelso Manado Town Square. This research conducted by a quantitative method and this research population is the buyers of wakai counterfeit shoes. By using an Independent Sample t-test, this research conducted a hypothesis is there is significant difference in utilitarian and hedonic value between male and female customers of Excelso Manado Town Square. Based on the result of this research, the data is normally distributed and homogenous. The result shows that there are no significant differences in utilitarian value and hedonic value between male and female customers of Excelso Manado Town Square. Findings suggest to develop strategies for enhancing utilitarian and hedonic value, which can increase the probability of customers revisiting to Excelso.Keywords: utilitarian value, hedonic value, gender